Presentation of Bilateral Peripheral Seventh Cranial Nerve Palsy in an HIV Patient. (5th August 2012) - Ruiz, Lisa M.; Kirmani, Batool
Abstract : Neurological manifestations in patients infected with human immunodeficiency virus can significantly increase overall morbidity and mortality. These complications are neither limited to a specific location in the nervous system nor a focal time period in the disease's progression. A literature review yielded several cases of peripheral facial palsy associated with HIV seropositivity, but few cases have been reported where the patient had bilateral peripheral facial palsy. In this paper, we present a patient with bilateral peripheral facial palsy and aseptic meningitis in the context of newly diagnosed HIV.